2011
DOI: 10.1016/j.ypmed.2011.07.017
|View full text |Cite
|
Sign up to set email alerts
|

Non-response bias in a web-based health behaviour survey of New Zealand tertiary students

Abstract: Respondents whose participation was hardest to elicit reported more risk behaviour. Assuming non-respondents' behaviour is similar or more extreme than that of late respondents, prevalence will have been substantially underestimated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
47
0
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(52 citation statements)
references
References 16 publications
4
47
0
1
Order By: Relevance
“…Moreover, even though data were kept separate from e-mail addresses and passwords, our requirement that students enter their e-mail address to enroll may have limited their participation. However, it should be noted that the percent of students who participated in the study is consistent with other college campus-wide surveys and established national surveys of alcohol and drug use (see Cunningham et al, 2012; Kypri, Samaranayaka, Connor, Langley, & Maclennan, 2011; Laguilles, Williams, & Saunders, 2011). However, university administrators who wished to utilize this approach as a primary strategy for addressing hazardous drinking among first-year students would likely require much higher participation rates.…”
Section: Discussionsupporting
confidence: 81%
“…Moreover, even though data were kept separate from e-mail addresses and passwords, our requirement that students enter their e-mail address to enroll may have limited their participation. However, it should be noted that the percent of students who participated in the study is consistent with other college campus-wide surveys and established national surveys of alcohol and drug use (see Cunningham et al, 2012; Kypri, Samaranayaka, Connor, Langley, & Maclennan, 2011; Laguilles, Williams, & Saunders, 2011). However, university administrators who wished to utilize this approach as a primary strategy for addressing hazardous drinking among first-year students would likely require much higher participation rates.…”
Section: Discussionsupporting
confidence: 81%
“…Our findings showed that the responders were less likely to engage in risk behaviours such as not using conspicuity aids and listening to music while riding. This is consistent with previous research, although unrelated to cycling, showing that lifestyle risk factors, such as smoking,9 16 17 38 39 alcohol abuse,12 40 physical inactivity16 40 41 and poor diet,40 are more common in non-responders or late responders.…”
Section: Discussionsupporting
confidence: 93%
“…However, the outcomes of responders and nonresponders were not significantly different in that study [26]. The outcomes of a study that relies on mailed surveys might be underestimated or overestimated as a result of nonresponders [15,18,31].…”
Section: Discussionmentioning
confidence: 76%